PENGARUH KEGIATAN EKSPERIMEN GUNUNG MELETUS TERHADAP KEMAMPUAN MEMAHAMI HUBUNGAN SEBAB-AKIBAT ANAK USIA 4-5 TAHUN DI KELOMPOK A RA-AHNAN KOTA BANDUNG - Heri Hidayat; Fadilla Ayuningtyas; Faiza Tsalimah Amatullah; Putri Dwi Lestari; Rifa Baidha Syahla (STKIP Subang, 2026)
The ability to understand cause-and-effect relationships is an important aspect of early childhood cognitive development. However, in reality, children's ability to understand simple cause-and-effect relationships has not yet developed optimally. Children still experience difficulties in explaining the causes of events, answering simple questions, and connecting actions with the consequences resulting from an activity. In addition, learning activities are still predominantly conducted through teacher explanations and do not sufficiently involve children in direct experiences through simple experiments. This study aimed to determine the effect of the volcano eruption experiment activity on the ability to understand cause-and-effect relationships among children aged 4–5 years in Group A of RA-Ahnan Bandung. This study employed a quantitative approach using a Pre-Experimental Design method. The research design was a One-Group Pre-test Post-test Design. The participants consisted of 7 children aged 4–5 years. Data were collected through observation, documentation, pre-tests, and post-tests. The collected data were analyzed using the Paired Sample T-Test. The results showed an improvement in children's ability to understand cause-and-effect relationships after receiving the treatment in the form of a volcano eruption experiment activity. This improvement was indicated by an increase in the mean score from 10.43 in the pre-test to 13.72 in the post-test. Furthermore, the Paired Sample T-Test results revealed a significance value (Sig. 2-tailed) of 0.000, which was lower than 0.05 (0.000 < 0.05). Therefore, it can be concluded that the volcano eruption experiment activity had a significant effect on improving the ability to understand cause-and-effect relationships among children aged 4–5 years in Group A of RA-Ahnan Bandung.